استقرار اليمن في ظل الدور الخليجي بعد عاصفة الحزم وإعادة الأمل: دراسة تحليلة - هاجري، محمد نويمي (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
This research deals with the issue of stability of Yemen in the light of the Gulf role after the 'asifah al-Hazm (The storm of firmness) and I'adat al-Amal (Return of the hope), the two military operation led by Saudi Arabia. The study therefore highlights: the history of Yemen from the BC until the modern history, the end of the era of the Zaydi Imamate and the beginning of the republican rule, the consequences of unity between the two Yemenite parties, the reasons that led to the disunity and weakness of Yemeni society, as well as the regional and international role that contributes to its instability and backwardness. The paper also discusses the situation of Yemen before and during the revolution of February 2011, and the reasons that hastened the uprising of Yemenis against the former President 'Ali 'Abdullah Salih, after 33 years on the throne of presidency in Yemen. Furthermore, the research addresses the role of 'asifah al-Hazm and I'adat al-Amal as well as their consequences on the present situation of Yemen. The researcher uses the historical approach to uncover the root causes and historical factors of the instability of Yemen over the previous years, the descriptive approach for the accurate description of the crisis in Yemen, and lastly, the statistical approach is adopted for the collection and analysis of statistical results from this crisis, and then for the deduction of the expected results. The researcher reaches some conclusions; one of which is the big responsibility of Arab Gulf countries for the present situation of Yemen, as well as the great contribution of the Sa'ada Six Wars between the former President Saleh and Houthi to the instability of Yemen, besides the poor standard of living, increase of unemployment, spread of corruption, increase of poverty and violation of human rights. Likewise, the revolution Arab Spring in Tunisia, Egypt, Libya and Syria has contributed a lot to the incitement of Yemeni revolution. Secondly, the seizure of the capital city Sana'a by Ansar Allah group on 21 December, 2014 was facilitated by the former President Ali Saleh, which eventually led to the outbreak of 'asifah al-Hazm on 26 March 2015 that complicated the Yemeni affairs. Finally, the operation of I'adat al-Amal began on April 22, 2015, which is still going on without achieving the goals for which it was launched.